1998
DOI: 10.1007/s001470050123
|View full text |Cite
|
Sign up to set email alerts
|

Dual renal grafts: expansion of the donor pool from an overlooked source

Abstract: This is a review of the emerging practice of dual renal allografting. In the setting of the expanded criteria cadaveric (and usually older) donor with inadequate function to allow single kidney transplantation, both kidneys have been transplanted into a single recipient. The recipient and donor have often been matched for age and size as dictated by the concept of nephron dosing. The reported results of dual grafting are excellent and statistically comparable to contemporaneous single cadaveric grafts. Criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Nephrotoxicity of calcineurin inhibitors can further compromise nephron mass and long‐term function. Doubling the nephron mass by transplanting the kidneys en bloc might overcome these problems (17–21). The ESP allocation scheme therefore included the option of transplanting both kidneys to a single recipient in cases in which the donor creatinine clearance was below 70 mL/min.…”
Section: Discussionmentioning
confidence: 99%
“…Nephrotoxicity of calcineurin inhibitors can further compromise nephron mass and long‐term function. Doubling the nephron mass by transplanting the kidneys en bloc might overcome these problems (17–21). The ESP allocation scheme therefore included the option of transplanting both kidneys to a single recipient in cases in which the donor creatinine clearance was below 70 mL/min.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that there may be reluctance on the part of transplant centers due to concerns about the increased risk of surgical complications, the prolonged warm and cold ischemic time and associated risk of DGF, and the uncertainty in determining which organs are suitable for single versus dual use. Longer time under anesthesia, and twice the number of dissections and vascular anastomoses, may contribute to a higher surgical risk with DKT (18). It is important to note, however, that since the first reported DKT in 1996 (19), there have been various surgical techniques, including unilateral placement of both kidneys (20), which successfully minimize the length of surgery and may ameliorate some of these concerns.…”
Section: Which Kidneys Should Be Used For Dkt?mentioning
confidence: 99%
“…7 However, subsequent analyses of these patients reveals that the recipients of DKTs from donors 54 to 60 years old had low serum creatinine levels up to 2 years after transplant and that may mean that these kidneys could have been used for an SKT. 8 Singh and associates 9 found that donors with an eGFR of 1.2 mL/s for a DKT was a better discriminator kidney transplant function than was an eGFR of 1.5 mL/s. In a recent prospective study, Snanoudj and associates 10 found that a donor eGFR between 0.5 and 1.0 mL/s was easily applicable to allocate ECD kidneys from donors over 65 years of age for a DKT.…”
Section: Introductionmentioning
confidence: 99%